The Role Of Local Champions In The Development Of Community Based Tourism In Ponggok Village, Klaten - Melati Fitra Aziza; Ratu Dika Kartika; Bangga Prameswara; Alhilal Furqan (Journal Research of Social Science, Economics, and Management, 2023)
Ponggok Village located in Klaten-Central Java is one of the villages that has been named the Best National Tourism Village in 2017 in the category of Community Empowerment from the Ministry of Villages, Development of Disadvantaged Regions and Transmigration, besides being named one of the richest villages in Indonesia with revenues reaching 14.5 billion in 2019 (goodnewsindonesia.com) of course, this achievement cannot be separated from the role of the local champion of Ponggok Village, Thanks to the initiation of the local champion of Ponggok village to be very successful and prosper its community, ponggok village also applies Community based tourism, local people are not only spectators, but as tourism actors and enjoy the impact directly, this article discusses the role of local champions seen from the concept of TALC butler (1980), analyzes each phase of the development of Ponggok village tourism and the involvement of local champions in it, In addition, it divides the role of local champions into 3 categories, namely facilitators, mediators and mobilizers